PERUBAHAN MATA PENCAHARIAN PETANI PADI SAWAH MENJADI PETANI KARET - Sumiyem Sumiyem; Nani Suwarni; Sugeng Widodo (JPG (Jurnal Penelitian Geografi), 2013)
The low rice production caused by the limited area of arable land and the low price of paddy rice which led farmers to plant rubber trees, in addition to easy marketing of rubber and rubber farmers incomes greater. This research study aims to examine changes in the livelihoods of rice farmers into rubber farmers in the village of Jaya district Bhakti Mesuji Komering Ogan Ilir regency period 1994-2003.  The method used is descriptive method, whereas the data collection technique used is observation, documentation and interviews and data analysis techniques used are based on a percentage analysis of the frequency table is simple. The population in this study as many as 198 households and a sample taken at 50 or 25% of the farmers of the existing population and this study is a research sample.  These results indicate that 1). A total of 28 or 56% which has a land area is 22 or 44% and having a narrow area. 2). Sebayak 26 or 54% of the production of low rice farming and 24 or 48% higher production of rice farming. 3). As many as 43 or 86% said the low price of rice led them to plant rubber and 7 or 14% said the low price of rice is not the cause of their planting rubber. 4). As many as 48 or 96% said quickly and easily sell their rubber plant is one of the causes of their rubber plant and a 2 or 4% said quickly and easily sell their rubber plant is not one of them causes the rubber plant. 5). As many as 26 or 52% of the rubber farmers have income per year is greater than or equal to Rp.41.794.800; - and 24 or 48% rubber farmers have an income per year is less than Rp.41.794.800; -.Key wordt: Lowland Rice Production, Rice Selling Price, Marketing Rubber, Rubber Farmers Income